Advances and New Perspectives in Marine Biotechnology Marine Animals & Plants - Paul Long (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2015)
As the Century of Biology begins to bear fruit, through the translation of predictive biological understanding into applications that enhance the human condition and maintain biodiversity, the almost infinite potential of marine biological resources will be unlocked. Although Marine Biotechnology already has delivered products for medicine, food, bioenergy, nanomaterials, and bioremediation, less than 5% of our vast oceanic environment has been explored. Marine Biotechnology is a scientifically and economically expanding enterprise that is poised to harness the enormous but uncharted functional diversity of marine life, with its novel and rich array of biodesigns and biosynthetic capabilities. From this pursuit comes new genes, chemicals, materials, and inspirations for the benefit of industry, nutrition, and medicine, and which enable the sustainable use and management of the world's oceans. This Special Issue in Marine Drugs highlights the cutting-edge developments in Marine Biotechnology with a collection of papers written by authors who are leading experts in the field, including selected papers from the 10th International Marine Biotechnology Conference (IMBC-2013), the premier meeting in marine biotechnology, which is held under the auspices of the International Marine Biotechnology Association.